Multi-criteria Decision Making: A Systematic Review - Azhar N.A.; Radzi N.A.M.; Ahmad W.S.H.M.W. (Bentham Science Publishers, 2023)
Complex networks; Site selection; Surveys; Analytical Hierarchy Process; Analytical network process; Decisions makings; Electre; Industrial decision making; Multi criteria decision-making; Multicriteria decision-making; Multicriterion decision makings; Network process; PROMETHEE; Topsi; Vikor; Decision making